LAKE FROG (PELOPHYLAX RIDIBUNDUS) AND GREEN FROG (BUFOTES PEWZOWI) SPECIES DESCRIPTION IN FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
In order to study the amphibians of the Ferghana Valley, observation work was carried out in several natural and geographical points of the valley and around the residential areas. As a result of observations, species belonging to the class of aquatic and terrestrial inhabitants were registered. Bufotes pewzowi and pelophlylax ridibundus have a wide distribution area among the registered species, and as a result of empirical research, about 10 of their individuals were recorded. It has been confirmed that Bufotes pewzowi is a synanthropic species that can also be found in human settlements. Valuable information on the systematics and species description of Bufotes pewzowi and Pelophlylax ridibundus is provided below.